The Effect Of Distribution, Digital Marketing And Consumers On Interest In Buying Korean Music Album In Students - Yusnidar, Cut; Boihaki, Boihaki; Isnaini, Teuku; Azzuhra, Muslimah (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study aims to determine